1994
DOI: 10.1103/physrevb.50.1337
|View full text |Cite
|
Sign up to set email alerts
|

Deformation superstructures, tweed, and oxygen-vacancy ordering associated with phase transformations inYBa2Cu3

Abstract: A theoretical technique is described, employing Monte Carlo simulation, which allows the investigation of strain effects associated with transformations in solids. The method applies a grand canonical stress ensemble in the study of elasticity during phase evolution in YBa2Cu30, where both oxygen occupancy and atomic positions in the basal plane, as we11 as total sample volume, can vary. Quenching experiments yield both metastable +2ao X +2ao superstructures from short-wavelength modulations and a tweed textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The time-dependent spatial distributions of oxygen atoms on two sublattices of the CuO plane were numerically simulated by means of the standard Monte-Carlo method with Metropolis probability distribution of energy changes [21][22][23][24]. We employed the so-called ANNNI approach, taking into account two types of repulsion potential between the nearest oxygen atoms and one type of attraction potential between the nearest chain oxygen atoms via the Cu atom orbital located between them.…”
Section: Monte-carlo Modelling and Flicker Noise Sources On The F −T mentioning
confidence: 99%
See 1 more Smart Citation
“…The time-dependent spatial distributions of oxygen atoms on two sublattices of the CuO plane were numerically simulated by means of the standard Monte-Carlo method with Metropolis probability distribution of energy changes [21][22][23][24]. We employed the so-called ANNNI approach, taking into account two types of repulsion potential between the nearest oxygen atoms and one type of attraction potential between the nearest chain oxygen atoms via the Cu atom orbital located between them.…”
Section: Monte-carlo Modelling and Flicker Noise Sources On The F −T mentioning
confidence: 99%
“…An analysis of the YO 1.5 -CuO-BaO chemical system in terms of geometric thermodynamics [36] has shown that the Gibbs potential G of the (123) phase should be reduced through formation of non-equilibrium defects by ∼50 kJ/gatoms, i.e. by (20)(21)(22)(23)(24)(25)%. There are probable mechanisms of structure stabilization through formation of a defect 235 ortho-phase [32,37].…”
Section: Structure and Composition Of Ybco Filmsmentioning
confidence: 99%